Genotyping and Whole-Genome Resequencing of Welsh Sheep Breeds Reveal Candidate Genes and Variants for Adaptation to Local Environment and Socioeconomic Traits - Sweet-Jones, James; Lenis, Vasileios Panagiotis; Yurchenko, Andrey A.; Yudin, Nikolay S.; Swain, Martin; Larkin, Denis M. (Frontiers in Genetics, 2021)
Background Advances in genetic tools applied to livestock breeding has prompted research into previously neglected breeds adapted to harsh local environments. One such group are Welsh mountain sheep breeds, which can be farmed at altitudes of 300 m above sea level but are considered to have low productive value because of their poor wool quality and small carcass size. This is contrary to lowland breeds which are more suited to wool and meat production qualities, but do not fare well on upland pasture. Herein, medium-density genotyping data from 317 individuals representing 15 Welsh sheep breeds was used alongside whole-genome resequencing data of 14 breeds from the same set to scan for signatures of selection and candidate genetic variants using haplotype and SNP-based approaches. Results Haplotype-based selection scan performed on genotyping data pointed to strong selection in the regions of GBA3, PPARGC1A, APOB, and PPP1R16B genes in Upland breeds, and RNF24, PANK2, and MUC15 in Lowland breeds. SNP-based selection scan performed on resequencing data pointed to missense mutations under putative selection relating to local adaptation in Upland breeds with functions such as angiogenesis (VASH1), anti-oxidation (RWDD1), cell stress (HSPA5), membrane transport (ABCA13 and SLC22A7), and insulin signalling (PTPN1 and GIGFY1). By contrast genes containing candidate missense mutations in Lowland breeds related to cell cycle (CDK5RAP2), cell adhesion (CDHR3), and coat colour (MC1R). Conclusions We found new variants in genes with potentially functional consequences to adaptation of local sheep to their environments in Wales. Knowledge of these variations is important for improving adaptative qualities of UK and world sheep breeds through marker-assisted selection.